Kehidupan Masyarakat Multi Agama Desa Bulurejo Purwoharjo Banyuwangi dalam Membangun Kerukunan Hidup Antar Umat Beragama - Harjianto Harjianto; Intan Daurotus Mukaromah; Bayu Indra Permana (Universitas Batanghari Jambi, 2020)
Religious harmony is a dynamic pillar of national harmony that must be maintained from time to time. Bulurejo village is a unique village because here there are many differences but they can live in harmony and side by side. In the village of Bulurejo the people are multi-religious, namely Islam, Hinduism, Christianity, Catholicism and Budha who live side by side and blend into one. The diversity that exists is one of the main advantages of the Village of Bulurejo. The aim of this research is to find out the life of the people in the village of Bulurejo in building harmony between religions, as well as knowing the forms of activities that describe the harmony of the religious community in the village of Bulurejo. This type of research is descriptive qualitative, with a phenomenological approach to the subject of village governance, religious leaders, and community leaders. The results of this study are the Bulurejo Village is a multi-religious village that has a diversity of religions and cultures. Bulurejo village has a religious harmony which can be said to be very good. This is indicated by togetherness in everyday life and doing various forms of activities carried out together including 1). Interfaith meetings conducted every three months; 2) Village cleaning activities are followed by all community members: 3). Religious activities in the implementation involve other people such as religious activities of Muslims, Hindus, Christians,Catholics, and Buddhist: 4). Activities commemorating the Republic of Indonesia Anniversary.